The Influence of Internet of Things (IoT), Digital Payment Systems, and 24/7 Customer Support Services on Improving Tourist Experience at Tourism Destinations in Bali, Indonesia - Zunan Setiawan; Afen Prana Utama Sembiring; Arnes Yuli Vandika; I Wayan Adi Pratama; Ni Desak Made Santi Diwyarthi (West Science Social and Humanities Studies, 2024)
This study investigates the influence of Internet of Things (IoT), digital payment systems, and 24/7 customer support services on improving travelers' experiences in tourism destinations in Bali, Indonesia. Using a quantitative approach, data were collected from 200 respondents through a structured Likert scale questionnaire, with analysis conducted using Structural Equation Modeling-Partial Least Squares (SEM-PLS 3). The results show that all three factors positively and significantly contribute to enhancing tourists' experiences, with 24/7 customer support services having the strongest impact, followed by digital payment systems and IoT. The findings highlight the importance of continuous customer support, secure and convenient digital transactions, and seamless IoT-enabled services in creating a positive tourism experience. These insights provide practical implications for tourism operators and policymakers in Bali, underscoring the need for technological investments to meet modern travelers' expectations.